Penggunaan media video dalam meningkatkan kualitas mengajar guru di sekolah - Deca Aisyah; Frety Febriyenti (Journal of Pedagogy and Online Learning, 2022)
This article analyzes the needs of teachers in an effort to improve the quality of teacher teaching by using technology and information through video media. Learning video media is a form of technology that is indispensable for teachers to support the successful implementation of effective and efficient learning. This is because learning video media can increase students' attention and interest in learning. The purpose of this study is to increase the use of instructional video media in the teaching and learning process and to improve the teaching quality of teachers in schools. The method used is descriptive quantitative method using quantitative data analysis techniques. The data collection technique used is a survey. Based on the data obtained, the results of this study indicate that 90% of teachers have difficulty in making learning media. In addition, 75% of teachers have limitations in the use of IT.